Relevance Theory and Muqtadha al-Hal: Toward a Pragmatic Balaghah Framework for Arabic Discourse Analysis - Berti Arsyad; Chaterina P. Doni (Yayasan Daarul Qimmah Gorontalo, 2026)
This study discusses the relationship between Relevance Theory in modern pragmatics and muqtadha al-hal in Arabic Balaghah as a basis for developing a pragmatic framework for Arabic discourse analysis. The discussion is motivated by the need to reinterpret Balaghah not only as a theory of linguistic beauty, but also as a contextual and communicative theory of meaning. This study aims to identify the conceptual convergences and differences between Relevance Theory and muqtadha al-hal and to formulate an integrative model called pragmatic Balaghah. Using a comparative literature review, the study analyzes scholarly works on pragmatics, cognitive inference, Arabic rhetoric, Ilm al-Ma‘ani, Qur’anic discourse, literary criticism, and text interpretation. The findings show that both frameworks emphasize context, speaker intention, audience reception, and communicative effectiveness. However, Relevance Theory is more receiver-oriented, focusing on inference, cognitive effect, and processing effort, whereas muqtadha al-hal is more speaker-oriented, focusing on rhetorical appropriateness and situational fit. The study concludes that pragmatic Balaghah offers a non-reductive framework for Arabic language studies, Arabic literature, Qur’anic discourse analysis, translation studies, and Islamic communication.